2019
DOI: 10.1016/j.jpainsymman.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Severity, and Correlates of Symptoms of Anxiety and Depression at the Very End of Life

Abstract: Context. Rates of psychological symptoms for patients with serious illness are high, but there has been limited research investigating psychological symptoms at the very end of life (EOL). Objectives. To better understand the prevalence, severity, and correlates of psychological distress at the very EOL. Methods. This retrospective cross-sectional study utilized caregiver proxy interviews. Caregivers were contacted after their care recipient recently died while receiving home hospice care and invited to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…When present, it was judged as moderate to severe. This is in line with the study of Kozlov et al, 16 where 47% of the caregivers of patients receiving hospice care at home scored their anxiety as 4 or higher on the Edmonton Symptom Assessment Scale. However, these caregivers were asked to retrospectively fill out the Edmonton Symptom Assessment Scale 2 to 3 weeks after the patient died.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When present, it was judged as moderate to severe. This is in line with the study of Kozlov et al, 16 where 47% of the caregivers of patients receiving hospice care at home scored their anxiety as 4 or higher on the Edmonton Symptom Assessment Scale. However, these caregivers were asked to retrospectively fill out the Edmonton Symptom Assessment Scale 2 to 3 weeks after the patient died.…”
Section: Discussionsupporting
confidence: 91%
“…The anxiety of the patient also had an impact on the life of the informal caregivers. This was also found in the study of Kozlov et al 16 They reported that anxiety of the patients who received hospice care at home was associated significantly with a higher caregiver burden.…”
Section: Discussionsupporting
confidence: 76%
“…About the theme [Care of nurses], nurses with visiting medical treatments worry about the mental health of a patient and caregiver, a visiting nurse proposes mental care. Kozlov, et al [5] showed that home hospice patients experience moderate-to-severe symptoms of anxiety and depression in the last week of life. Since family caregivers worry about the physical and emotional symptoms at the very end of care, support for this point may be important.…”
Section: Perception Of Nurses For Home Hospice By Visiting Medical Trmentioning
confidence: 99%
“…Family caregivers of advanced cancer patients feel distressed along with sadness, sorrow and exhaustion, or anxiety and depression [4]. Family caregivers at home hospice had moderate-tosevere anxiety or similar symptoms [5], and they experienced crisis, such as patient signs and symptoms, emotional distress, and burdens [6]. Also, Reblin, et al [7] showed that caregivers had moderate levels of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Although patients and caregivers commonly express satisfaction with hospice care, there remain challenges in achieving this aim (Jenkins & Codling, 2013). Although estimates of prevalence vary, a notable number of hospice patients experience depression and anxiety, and there are grounds to think such conditions are underreported (Hayes et al, 2017; Irwin et al, 2008; Kozlov et al, 2019). In addition, loneliness and lack of relational connectedness impact hospice patients’ quality of life (Bale et al, 2016; Rokach, 2016; Sawyer et al, 2019; Untas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%